Pengaruh Kepercayaan dan komitmen Terhadap Kinerja Rantai Pasokan Toko Kelontong Jaringan SRC - Martina Dwiastuti; Diqbal Satyanegara (Universitas Sultan Ageng Tirtayasa, 2022)
The purpose of this research is to measure the influence of trust and commitment to supply chain performance of SRC’s grocery network. Two proposed hypotheses are tested : first, testing the infuence of trust to supplye chain performance; second, testing the influence of commitment to supply chain performance. This research apply quantitative method whereas the population are the network of SRC in Cikupa Tangerang, Banten Indonesia. Samples are chosen with probability sampling consist of 61 respondents. Data analized with SmartPLS 3.3.7. The result is: 1) Trust has a positive non significant influence to supply chain performance, and 2) Commitment has a positive and significant to supply chain performance.